2007
DOI: 10.1007/s11064-007-9292-2
|View full text |Cite
|
Sign up to set email alerts
|

NTPDase and 5′-nucleotidase Activities of Synaptosomes from Hippocampus of Rats Subjected to Hyperargininemia

Abstract: ATP is an important excitatory neurotransmitter and adenosine acts as a neuromodulatory structure inhibiting neurotransmitters release in the central nervous system. Since the ecto-nucleotidase cascade that hydrolyzes ATP to adenosine is involved in the control of brain functions and previous studies realized in our laboratory have recently reported that acute administration of Arg decreases the NTPDase and 5'-nucleotidase activities of rat blood serum, in the present study we investigated the effect of argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These results differ from previous studies from our laboratory that showed that other guanidine The interaction of GAA with NTPDase and 5 0 -nucleotidase activities was determined using the Lineweaver Burk [41] double reciprocal plot, by plotting 1/V against 1/S analysed over a range of nucleotides concentrations: ATP and ADP (10-1,000 lM) and AMP (20-2,000 lM) in the absence and in the presence of GAA compounds such as N-acetylarginine, arginic acid and homoarginine, which are accumulated in hyperargininemic patients, increased NTPDase and 5 0 -nucleotidase activities in synaptosomes from the cerebral cortex [49]. Taken together, these findings suggest that guanidine compounds have heterogeneously effects in the purinergic signaling in the brain areas, a fact that that can be explained by the different chemical structure of these compounds [49,50]. NTPDase and 5 0 -nucleotidase are the most relevant ectoenzymes involved in adenine extracellular nucleotide hydrolysis [4,6].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results differ from previous studies from our laboratory that showed that other guanidine The interaction of GAA with NTPDase and 5 0 -nucleotidase activities was determined using the Lineweaver Burk [41] double reciprocal plot, by plotting 1/V against 1/S analysed over a range of nucleotides concentrations: ATP and ADP (10-1,000 lM) and AMP (20-2,000 lM) in the absence and in the presence of GAA compounds such as N-acetylarginine, arginic acid and homoarginine, which are accumulated in hyperargininemic patients, increased NTPDase and 5 0 -nucleotidase activities in synaptosomes from the cerebral cortex [49]. Taken together, these findings suggest that guanidine compounds have heterogeneously effects in the purinergic signaling in the brain areas, a fact that that can be explained by the different chemical structure of these compounds [49,50]. NTPDase and 5 0 -nucleotidase are the most relevant ectoenzymes involved in adenine extracellular nucleotide hydrolysis [4,6].…”
Section: Discussionmentioning
confidence: 91%
“…The values of inhibition constant (K i ) were obtained using Cornish-Bowden plots of S/V versus [I] [43]. IC 50 , was estimated at fixed substrate concentration the according to the Dixon and Webb [44] plot using 1/V versus [I].…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…In contrast, studies demonstrated that arginine in vitro decreased NTPDase and 5'-nucleotidase activities in rat hippocampus. Rats subjected to intracerebroventricular arginine administration showed a reduction in ATP, ADP and AMP hydrolysis in rat hippocampus and serum and L-NAME, an inhibitor of nitric oxide synthase, prevented such effects [31,34]. Proline, an amino acid accumulated in hyperprolinemia, did not alter nucleotide hydrolysis when added to enzyme assays, but when administered acutely or chronically, it decreased ATP hydrolysis in rat cerebral cortex synaptosomes; ADP and AMP hydrolysis were not altered by proline administration [33].…”
Section: Inborn Errors Of Metabolism and Ectonucleotidasesmentioning
confidence: 93%